Mitral valve prolapse: American versus European guidelines : which one is better - Brito, J. (2022)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2021. For permissions please email: Journals.permissions@oup.com. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)